SPECIFIC ANTI RULE AVOIDANCE (SAAR): HOW DOES IT AFFECT TAX AVOIDANCE? - Agustin Dwi Haryanti; Firda Ayu Amalia; Eny Suprapti (Jurnal Reviu Akuntansi dan Keuangan, 2020)
This study aims to empirically prove the influence of the Specific Anti Avoidance Rule (SAAR), namely transfer pricing, thin capitalization, controlled foreign corporations (CFCs), the use of tax heaven countries, and treaty shopping on tax avoidance. SAAR is a special rule to minimize tax avoidanceThe sample in this study is multinational companies listed on the Indonesia Stock Exchange in the 2015-2017 period. The method used is multiple linear regression with SPSS version 24. The results show that transfer pricing, thin capitalization, controlled foreign corporations (CFCs), utilization of tax heaven countries, and treaty shopping have no effect on tax avoidance. The absence of influence of the five independent variables on tax avoidance is due to the sample company data and also the proxy used. The results of the study are expected to contribute especially to the government regarding whether SAAR is sufficient to minimize and overcome tax avoidance and can also be a consideration for the government to implement the General Anti Avoidance Rule (GAAR) to cover the weaknesses of SAAR.